2019
DOI: 10.1186/s12891-019-2979-0
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of planar anteversion measurements using anteroposterior radiographs

Abstract: BackgroundSeveral methods using simple anteroposterior (AP) radiographs have been suggested for the measurement of anteversion of the cup component after total hip arthroplasty. Herein, we compared six widely used anteversion measurement methods using two different types of AP radiograph, the conventional pelvis AP and hip-centered AP radiographs, to identify the measurement method and the type of radiograph that would provide the highest accuracy and reliability.MethodsWe developed two custom-made bi-planar a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 25 publications
(39 reference statements)
0
20
0
Order By: Relevance
“…On the other hand, AI over 45° reduces adduction and rotation. There is also higher wear of acetabular polyethylene when the AI is over 45° [ 13 , 14 ]. It cannot be univocally stated, without additional studies, what is a safe range for AI [ 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, AI over 45° reduces adduction and rotation. There is also higher wear of acetabular polyethylene when the AI is over 45° [ 13 , 14 ]. It cannot be univocally stated, without additional studies, what is a safe range for AI [ 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Because of that, plain radiographs are in common use. Plenty of methods can be used to measure anteversion, and there is no validated and most efficient one [ 14 ]. This is due to the fact that pelvic tilt has a greater impact on measuring anteversion on anteroposterior radiographs rather than determining abduction angle on anteroposterior radiographs.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it can be hypothesized that there could be up to six degrees of difference depending on how the X-ray is acquired. The authors have chosen to use Lewinnek's method of anteversion measurement as studies have shown high inter- and intra-observer reliabilities and no significant differences in anteversion between measurements made on pelvis and hip-centered AP radiographs 28 29) . Lastly, there is a lack of clinical data at short- and long-term follow-up to determine if this accuracy in implant position translates to better clinical outcome in terms of reduced dislocation or revision rate.…”
Section: Discussionmentioning
confidence: 99%
“… 8 While computed tomography (CT) scanning accurately evaluates the component position and is regarded as the golden standard technique, 9 , 10 , 11 plain radiographs continue to be commonly used due to the relatively low cost and radiation exposure. 12 , 13 , 14 Anteroposterior (AP) pelvic radiography is the standard method used for inclination angle measurement. 15 The component version was generally measured using AP radiographs 12 , 16 , 17 or cross‐table lateral (CL) radiographs.…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 , 14 Anteroposterior (AP) pelvic radiography is the standard method used for inclination angle measurement. 15 The component version was generally measured using AP radiographs 12 , 16 , 17 or cross‐table lateral (CL) radiographs. 18 , 19 However, the optimal plain radiographic method for cup version measurement is not preferred.…”
Section: Introductionmentioning
confidence: 99%